Literature as a mode of thought: Derrida’s institution of différance - Ó Fathaigh Cillian (Filozofija i Društvo)
In this article, I argue that literature represents a privileged modality for thinking institutionality in Derrida’s work and, moreover, that literature represents a model for institutions. The first section presents Derrida’s understanding of literature as anti-essentialist and a mode of experience which resists the transcendence of identity. In the second section, I propose that literature attends to its own fragility, lacking any definite foundation or external referent. I then consider the political implications of this position, demonstrating that literature not only encourages us to attend to its own fragile foundations, but also the foundations of socio-political institutions in general. It achieves this attention through its specific relationship to performative language. In the fourth section, I argue that literature reveals institutions as an effect of différance; rather than understanding différance as an infinite delay, institutions emerge in the process of différance. Literature underscores the inescapability of institutions. Our aim, as Derrida stresses, should not be to do away with institutions, but to form a new relation to institutions. I conclude by outlining some of these implications for literature as an institution which can serve as a model for the new relation to institutionality that Derrida valorises.